2020
DOI: 10.1177/2053951720952088
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 is spatial: Ensuring that mobile Big Data is used for social good

Abstract: The mobility restrictions related to COVID-19 pandemic have resulted in the biggest disruption to individual mobilities in modern times. The crisis is clearly spatial in nature, and examining the geographical aspect is important in understanding the broad implications of the pandemic. The avalanche of mobile Big Data makes it possible to study the spatial effects of the crisis with spatiotemporal detail at the national and global scales. However, the current crisis also highlights serious limitations in the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
60
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 40 publications
0
60
0
5
Order By: Relevance
“…Finally, our study demonstrated how mobile phone data could be used to provide important insights across spatial scales and prolonged time periods that are able to support situational awareness [35,42,49]. In particular, we demonstrated how inherently dynamic social phenomenon of multi-local living could be revealed and timely monitored with data products of mobile network operators.…”
Section: Feasibility Of Mobile Phone Data In Crisis Managementmentioning
confidence: 72%
See 2 more Smart Citations
“…Finally, our study demonstrated how mobile phone data could be used to provide important insights across spatial scales and prolonged time periods that are able to support situational awareness [35,42,49]. In particular, we demonstrated how inherently dynamic social phenomenon of multi-local living could be revealed and timely monitored with data products of mobile network operators.…”
Section: Feasibility Of Mobile Phone Data In Crisis Managementmentioning
confidence: 72%
“…These include the varying spatial and temporal resolutions of each data source [48] and difficulties to integrate them to reveal mobility dynamics on relevant scales [35]. Furthermore, access to data, the capacity to process complex data and establish the necessary interdisciplinary teams and collaborations, lack of political will, and concerns about data privacy and protection have remained challenges, and hindered widespread use of mobile phone data in operational decision making [42,49].…”
Section: Human Mobility Mobile Phone Data and Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…This study has used mobile phone data to provide rigorous evidence for an link between socioeconomic status (SES) with mobility reduction during the Spring 2020 lockdown in England, while considering the potentially confounding effects of other factors and “recognising the fundamental spatiality of the current COVID-19 crisis” (Poom et al, 2020, p. 5). Two main conclusions can be drawn along with a future research direction.…”
Section: Discussionmentioning
confidence: 99%
“…As emphasised by Poom et al (2020), the current global crisis is clearly spatial in nature -the virus outbreak, hot spots, mitigation measures, closed borders, quarantines and related societal impacts are all profoundly about distance, separation and space. This has offered geographers opportunities for analyses of the relevant issues through a geographic lens and predestined them to play a significant role in the fight against the pandemic (see Aalberset et al, 2020;Rose-Redwood et al, 2020).…”
mentioning
confidence: 99%